2019
DOI: 10.1093/poq/nfz041
|View full text |Cite
|
Sign up to set email alerts
|

The Polls—Trends

Abstract: Events such as the 2017 “March for Science” have brought greater attention to public attitudes toward science and scientists. Our analyses of recent poll data show that Americans’ confidence in scientists has been high for roughly 40 years (relative to other institutions), and that it is high even for controversial topics such as global warming and nuclear energy. International comparisons show broad similarities with individuals in Germany and the UK, including that trust in scientists can fluctuate depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 7 publications
1
59
0
Order By: Relevance
“…These behaviors directly contradict recommendations by both the CDC and NIH. In the U.S. there is a widening gap in trust in science and science-based recommendations based on political party 22 which may contribute to the observation here that Republicans are more likely to ignore recommendations about the COVID-19 response. In addition, the results reported here agree findings that there are political divisions over the role of scientific experts in policy matters 23 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These behaviors directly contradict recommendations by both the CDC and NIH. In the U.S. there is a widening gap in trust in science and science-based recommendations based on political party 22 which may contribute to the observation here that Republicans are more likely to ignore recommendations about the COVID-19 response. In addition, the results reported here agree findings that there are political divisions over the role of scientific experts in policy matters 23 .…”
Section: Discussionmentioning
confidence: 88%
“…In addition, there are well described patterns of health literacy based on education level, 20 and race 21 which may not be present in a homogeneous society such as China. Political party identification is associated with many attitudes and behaviors in the U.S. related to science and science-based recommendations 22,23 . Leaders from both major parties in the U.S. have reacted differently to the COVID-19 pandemic, likely influencing those who follow them 24,25 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are well described patterns of health literacy based on education level [20] and race [21], which may not be present in a homogeneous society such as China. Political party identification is associated with many attitudes and behaviors in the United States related to science and science-based recommendations [22,23]. Leaders from both major parties in the United States have reacted differently to the COVID-19 pandemic, likely influencing those who follow them [24,25].…”
Section: Surveymentioning
confidence: 99%
“…Instead, numerous surveys have found an association between conservative political ideology and a loss of trust both in science itself as well as in scientists (Hamilton, Hartter and Saito 2015; Krause et al 2019; Leiserowitz et al 2012; McCright et al 2013; Safford et al 2019). This distrust is exacerbated when scientists themselves engage in public policy debates (Brulle 2018; Milkoreit et al 2015; Motta 2018).The tendency of political polarization around scientifically-based warnings has been documented most recently with respect to the Covid-19 pandemic(Ballew et al 2020; Ellis 2020;Krause et al 2019; Pennycook et al 2020; Van Bavel et al 2020).In a recent study, we compared the impact of climate scientists with party leaders and military leaders, and found that climate scientists had relatively little positive impact on the Accepted for publication in Weather Climate and Society. DOI 10.1175/WCAS-D-19-0141.1.…”
mentioning
confidence: 99%